2021
DOI: 10.1038/s41598-021-84611-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals brown adipogenic reprogramming in chemical compound-induced brown adipocytes converted from human dermal fibroblasts

Abstract: Brown adipogenesis contributes to controlling systemic energy balance by enhancing glucose and lipid consumptions. We have previously reported chemical compound-induced brown adipocytes (ciBAs) directly converted from human dermal fibroblasts using a serum-free medium. In this study, genome-wide transcriptional analysis was performed in ciBAs in comparison with the control fibroblasts. A broad range of integrated gene expression was enhanced in functional groups including tricarboxylic acid cycle, electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…The RNA-Seq analysis revealed that Capsaicin activated not only UCP1 gene but also a series of metabolic genes involved in triglyceride metabolism, fatty acid metabolism, glycolysis pathway, and adaptive thermogenesis. Many of them were overlapped with genes activated during the direct conversion into ciBAs, as shown in our previous analysis 36 , indicating that these metabolic genes are closely associated with functions in brown adipocytes. In addition, this study revealed that Capsaicin activated mitochondrial biogenesis, oxygen consumption, glycolysis, glycerol recycling, and triglyceride accumulation.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The RNA-Seq analysis revealed that Capsaicin activated not only UCP1 gene but also a series of metabolic genes involved in triglyceride metabolism, fatty acid metabolism, glycolysis pathway, and adaptive thermogenesis. Many of them were overlapped with genes activated during the direct conversion into ciBAs, as shown in our previous analysis 36 , indicating that these metabolic genes are closely associated with functions in brown adipocytes. In addition, this study revealed that Capsaicin activated mitochondrial biogenesis, oxygen consumption, glycolysis, glycerol recycling, and triglyceride accumulation.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous report suggested that the direct conversion to ciBAs underwent genome-wide transcriptional changes similar to the adipocyte browning in AdMSCs 36 . In contrast, one of the most characteristic differences between them was the expression pattern of major uncoupling proteins.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, in [ 180 ], the authors created a dataset of 1933 antigen sequences from similar diseases (SARS, HIV, and EBOLA); then, they trained the XGBoost model (classification model) to predict the antibody that will affect the antigen. Other researchers [ 186 ] tried to predict effective anti-bodies from the future generation of COVID-19. They mutated the SARS antibody sequence and generated 2900 antibody sequences.…”
Section: The Study Taxonomymentioning
confidence: 99%